2016
DOI: 10.1128/aac.00710-16
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Alpha-Toxin and Protective Effects of Its Neutralization by a Human Antibody in Acute Bacterial Skin and Skin Structure Infections

Abstract: g Methicillin-resistant Staphylococcus aureus (MRSA) causes large-scale epidemics of acute bacterial skin and skin structure infections (ABSSSI) within communities across the United States. Animal models that reproduce ABSSSI as they occur in humans are urgently needed to test new therapeutic strategies. Alpha-toxin plays a critical role in a variety of staphylococcal infection models in mice, but its role in the pathogenesis of ABSSSI remains to be elucidated in rabbits, which are similar to humans in their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…Although alpha-toxin is a key virulence determinant in S. aureus pneumonia and skin and soft-tissue infections (20,26), bloodstream infections are likely more complex, with a more complicated interplay of virulence determinants involved (27)(28)(29)(30)(31). Consistent with this hypothesis, prophylaxis with an anti-alpha-toxin IgG alone significantly reduced disease severity in S. aureus pneumonia and skin infection models in mice and rabbits (6,8,20,21,26,(32)(33)(34) but did not protect against challenge by all isolates tested in a lethal bacteremia model (Table 2) (9). However, passive immunization with MEDI4893* combined with anti-ClfA MAb 11H10 or SAR114 provided improved strain coverage, indicating that targeting multiple virulence factors may be necessary to protect against systemic S. aureus diseases such as bacteremia ( Table 2; Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Although alpha-toxin is a key virulence determinant in S. aureus pneumonia and skin and soft-tissue infections (20,26), bloodstream infections are likely more complex, with a more complicated interplay of virulence determinants involved (27)(28)(29)(30)(31). Consistent with this hypothesis, prophylaxis with an anti-alpha-toxin IgG alone significantly reduced disease severity in S. aureus pneumonia and skin infection models in mice and rabbits (6,8,20,21,26,(32)(33)(34) but did not protect against challenge by all isolates tested in a lethal bacteremia model (Table 2) (9). However, passive immunization with MEDI4893* combined with anti-ClfA MAb 11H10 or SAR114 provided improved strain coverage, indicating that targeting multiple virulence factors may be necessary to protect against systemic S. aureus diseases such as bacteremia ( Table 2; Fig.…”
Section: Discussionmentioning
confidence: 82%
“…The latter would kill the bacteria but fail to neutralize the effects of the secreted AT that could be blocked by a toxin neutralizing antibody. Multiple studies from independent laboratories with different anti-AT mAbs have demonstrated additive or synergistic protective activity with multiple antibiotics in different S. aureus animal infection models (Foletti et al, 2013; Hua et al, 2015; Hua et al, 2014; Le et al, 2016). The results herein offer one possible explanation as to how targeting AT may contribute to enhanced protection from acute lethality on top of traditional antibiotic antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Given its importance in exacerbating infection severity, AT has been a clinical target, employing both monoclonal antibodies and small molecules. These therapies have had a marked effect on reducing disease severity in mouse and rabbit models of S. aureus skin infection(3335). Still, it is unclear whether targeting AT in an active or passive vaccination strategy will be effective as a single antigen, because S. aureus produces many other virulence factors that evade host defenses(36).…”
Section: Discussionmentioning
confidence: 99%